2001
DOI: 10.1002/ccd.1240
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium‐based coronarography in a patient with renal failure: First clinical report

Abstract: This article reports the use of gadolinium to perform a coronarography in a patient with renal insufficiency, unstable angina, and peripheral vascular disease. The examination was well tolerated and the images obtained of good quality. Cathet Cardiovasc Intervent 2001;54:68-69.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…15 The first study of CAG using Gd was in patients with renal insufficiency. [6][7][8] There are several limitations to the use of Gd as an X-ray contrast agent. First, it is inferior to iodinated agents for image contrast, although digital subtraction post-processing can resolve that problem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 The first study of CAG using Gd was in patients with renal insufficiency. [6][7][8] There are several limitations to the use of Gd as an X-ray contrast agent. First, it is inferior to iodinated agents for image contrast, although digital subtraction post-processing can resolve that problem.…”
Section: Discussionmentioning
confidence: 99%
“…1-5 However, only a few studies of using gadolinium for CAG have been reported and only its safety in patients with renal insufficiency has been discussed. [6][7][8] We report successful CAG using gadodiamide hydrate (Gd DTPA-BMA; Omniscan ® Nycomed, Oslo. Norway) in 3 patients with allergy to iodinated contrast media.…”
mentioning
confidence: 99%
“…Its elimination half-life is approximately 90 min (Bokhari et al, 2003). Coronary angiography using gadolinium as a contrast agent has been described (Sarkis et al, 2001;Bokhari et al, 2003;Ose et al, 2005). Patients with iodine-induced hyperthyroidism and unstable angina pectoris would in some cases require an intervention, but the use of iodinated contrast agent imposes a risk for thyrotoxic storm.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue, Sarkis et al [1] report the performance of coronary angiography utilizing gadodiamide in a patient with renal insufficiency and diabetes presenting with intractable angina. Gadolinium is a lanthanide (rare earth element) that has significant toxicity as a naked metal ion, but is well tolerated when complexed with electron donating ligands.…”
mentioning
confidence: 99%
“…Sarkis et al [1] have shown that it is possible to obtain reasonable imaging using standard angiographic technique. In unique situations this may be of clinical benefit, but the restriction of the amount of contrast coupled with the low concentration of available agents will challenge the ability of the angiographer to obtain adequate diagnostic study, let alone perform intervention, within labeled recommendations in all but the simplest cases.…”
mentioning
confidence: 99%